Imprensa e impressos para a civilidade da infância : representações e apropriações (Vitória na segunda metade do século XIX) - Rocha, Luciane Paraiso (2012)
The dissertation, developed under the PPGE/UFES, studies the representations of childhood that circulated in the capixabas newspapers, published in Victoria between the years 1849 and 1869, and the representations for childhood, circulated in print with the intent to educate and instruct, as some compendiums. We start from presumption that childhood is a social-historical-cultural construction and we elaborated the following question: representations of childhood and for the childhood that permeated the texts of capixabas intellectuals were entwined that political, economic and social? We hypothesized that the presence of representations of childhood in the texts of capixabas intellectuals (printed and press) was permeated by national and international text appropriating, resulting from the circulation of these representations. We conclude that the studied texts show the direction of movement of its representations and appropriations, with the goal of to form future adults and immersed citizens in a given reading of civility. Our principal sources were Correio da Victoria, A Regeneração, O Tempo e o Jornal da Victoria newspapers e Compendio da Grammatica Portugueza para uso das escolas primarias (Luis da Silva Alves de Azambuja Suzano), História de Simão de Nantua ou o mercador de feiras (Laurent de Jussieu) e Thesouro de meninos (Pedro Blanchard) compendiums. We based our research on the conceptual scheme of Roger Chartier, the Elias civility notions and Sirinelli intelectual notions. This research was sponsored by FAPES.